2007
DOI: 10.1162/jocn.2007.19.7.1104
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Sequential Effects of Stimulus- and Response-related Conflict and Stimulus-Response Repetition using Brain Potentials

Abstract: Conflict monitoring theory holds that detection of conflicts in information processing by the anterior cingulate cortex (ACC) results in processing adaptation that minimizes subsequent conflict. Applying an Eriksen f lanker task with four stimuli mapped onto two responses, we investigated whether such modulation occurs only after response-related or also after stimulus-related conflict, focusing on the N2 component of the event-related potential. Contrasting with previous findings, both stimulus- and response-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
89
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 36 publications
12
89
1
Order By: Relevance
“…Studies comparing neural signatures of stimulus and response conflict revealed inconsistent findings: fMRI recordings (van Veen, Cohen, Botvinick, Stenger, & Carter, 2001) and ERPs (van Veen & Carter, 2002) showed activations of the ACC exclusively during response conflict and not during stimulus conflict. In contrast, Wendt, Heldmann, Munte, and Kluwe (2007) reported an N2 effect in the ERP for both stimulus and response conflict that did not distinguish between conflict types.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Studies comparing neural signatures of stimulus and response conflict revealed inconsistent findings: fMRI recordings (van Veen, Cohen, Botvinick, Stenger, & Carter, 2001) and ERPs (van Veen & Carter, 2002) showed activations of the ACC exclusively during response conflict and not during stimulus conflict. In contrast, Wendt, Heldmann, Munte, and Kluwe (2007) reported an N2 effect in the ERP for both stimulus and response conflict that did not distinguish between conflict types.…”
Section: Introductionmentioning
confidence: 74%
“…Our results contrast to reports by van Veen et al (van Veen & Carter, 2002;van Veen et al, 2001) who conducted a letter flanker experiment and reported enhanced activity within the MFC only during response conflict but not during perceptual conflict in an fMRI study (2001). In an ERP study (van Veen & Carter, 2002), they replicated this finding with N2 enhancements only during response conflict trials whereas Wendt et al (2007) found N2 enhancements both for stimulus and response conflicts. In the latter study, however, the N2 effects did not dissociate between response and stimulus conflict.…”
Section: Mfc Theta Power During Perceptual and Response Conflictmentioning
confidence: 85%
“…Here it was recently shown that the Ne differed between healthy controls and symptomatic HD (Beste et al 2006) as well as between symptomatic and presymptomatic HD (Beste et al 2007b) but not between healthy controls and presymptomatic HD (Beste et al 2007a). It is still a matter of debate whether the Ne, supposed to reflect error processing (e.g., Falkenstein et al 1991;Ullsperger and von Cramon 2001), is comparable to the N2, reflecting conflict processing (e.g., Azizian et al 2006;Wendt et al 2007). The pattern of results regarding a similar reduction of the Ne and the N2 in HD suggests that the Ne and the N2 share common processes (see also : Yeung et al 2004).…”
Section: Conflict Processingmentioning
confidence: 91%
“…Chen et al, 2011;Z. Chen, Lei, Ding, Li, & Chen, 2013;Steinhauser & Hübner, 2009;Wendt, Heldmann, Münte, & Kluwe, 2007). Researchers have utilized congruent trials as a baseline to measure response conflict and have successfully differentiated response-and semantic-based conflict using distribution analysis (A.…”
mentioning
confidence: 99%